The Impact of the 'Scientific Traveler' Mobile App on Seventh Graders' Understanding of Natural Tourist Sites in Oman (Journal Of Educational and Psychological Researches, 2025)
This study investigated the impact of scientific concepts through using a gamification approach-based mobile application on the acquisition of scientific concepts, as well as the correction of relevant alternative perceptions about the most important natural tourism sites for seventh graders in the Sultanate of Oman.            Pre-post study was conducted using a quasi-experimental design. The sample consisted of 64 seventh-grade students, of which 33 students were assigned to be the experimental group, and 31 students were assigned to be the control group.A mobile application called "scientific traveler" was designed based on the principles of the gamification approach, and was implemented for the experimental group. Furthermore, two tests were created and administered as pre- and post-tests for both study groups: one for their alternative perceptions of the most significant natural tourism sites in Oman, with a reliability coefficient of 0.88, and another for their acquisition of scientific concepts, with a reliability coefficient of 0.77.The data collected  by using the suitable statistical tools, then analyzed. The results showed a statically significant difference between the experimental and control groups in favor of the experimental group. This difference at a level of (α= 0.05) in the acquisition of scientific concepts test. This study also found a statically significant difference at a level of (α= 0.05) between the mean score of the experimental group and the mean score of the control group in favor of the experimental group in alternative perceptions about the most important natural tourism sites in Oman.            The study recommends that science educators and tourism officials design mobile applications based on the principles of the gamification approach to support students' acquisition of scientific concepts, and to correct their perceptions about important natural tourism sites in Oman.